Meningkatkan Prestasi dan Keaktifan Belajar Siswa SMP Negeri 13 Madiun melalui Program Adiwiyata - Nartini Nartini; Darmadi Darmadi (Universitas Islam Negeri Sayyid Ali Rahmatullah Tulungagung, 2019)
Adiwiyata is one of the programs of the Ministry of the Environment to encourage the creation of knowledge and consciousness of residents in environmental preservation efforts by involving parents in learning. This paper discuss the increased of achievement and passion in learning, as well as the response of the students in class VIIF SMP Negeri 13 Madiun on the subject of the triangle and quadrilateral. The research method used is the Classroom Action Research (CAR). Data collected by test, observation, and question form. Data analysis using grade analysis of study, level of study, and the students attitude. The results showed: 1) Adiwiyata increase the achievements of students in class VIIF SMP Negeri 13 Madiun; 2) Adiwiyata increase the passion in learning of the student in class VIIF SMP Negeri 13 Madiun; 3) Student in class VIIF SMP Negeri 13 support adiwiyata program to improve learning achievements and passion in learning.